Impact of Saliva and Cariogenic Microbiota on the Chemotherapy-Induced Oral Mucositis in Oncopediatric Patients: A Preliminary Longitudinal Study - Raphael Cavalcante Costa; Paula Maria Maracajá Bezerra; Lecidamia Cristina Leite Damascena; Isabella Lima Arrais Ribeiro; Paulo Rogério Ferreti Bonan; Simone Alves de Sousa; Leopoldina de Fátima Dantas Almeida; Ana Maria Gondim Valença (Hindawi Limited, 2020)
This study aims to evaluate the salivary parameters and cariogenic microbiota of pediatric oncological patients and their correlation with severe oral mucositis (SOM). A preliminary longitudinal study included patients in the age range from 4 to 18 years (n = 26), with diagnosis of primary cancer, who were followed up before and after time intervals of two, five, and ten weeks of induction chemotherapy. Oral mucosa examinations were performed by means of the modified Oral Assessment Guide (OAG) by calibrated examiners (κ > 0.70). Saliva analysis (unstimulated saliva flow (USF), clinical saliva viscosity (CSV), and pH) and microbiological (total Streptococcus (TS) and Streptococcus of the mutans group (SMG)) tests were performed using unstimulated saliva. The data were analyzed by the Wilcoxon and Spearman Correlation tests (α = 5%). The patients were predominantly of the female sex (n = 15; 57.7%), adolescents (n = 15; 57.7%), and patients with hematological tumors (n = 21; 80.8%). SOM was more frequent in the tenth week (n = 7; 28.6%). The values of USF, CSV, pH, TS, and SMG were not changed by the institution of chemotherapy (p>0.05). These values were correlated with SOM and the time, TS and SMG, and CSV and SMG. The salivary and microbiological parameters investigated did not influence the severity of oral mucositis in the pediatric patients oncological..